STUDI KOMPARASI: TAFSIR KLASIK TURJUMAN AL-MUSTAFID AS-SINGKILI DAN TAFSIR MODERN AL-AZHAR BUYA HAMKA (Kajian Mufasir Kawasan Asia Tenggara) - Anisa; Mohammad Umar Said; Singgih Prayogo; Luqman Abdul Jabbar; Jimmy Malintang (Qolamuna : Jurnal Studi Islam, 2026)
This study conducts a comparative analysis of two influential Qur’anic commentaries in the Malay-Indonesian archipelago: Turjuman al-Mustafid by Abdur Rauf as-Singkili (17th century) and Tafsir al-Azhar by Buya Hamka (20th century). These works represent two distinct phases in the development of Qur’anic interpretation— the classical period characterized by reliance on transmitted knowledge (riwāyah), literalism, and pedagogical-sufi traditions, and the modern period marked by rationality, contextual reading, and a humanistic adabī-ijtima‘ī approach. Using a comparative textual analysis, this research examines the historical background of the exegetes, their epistemological sources, interpretative methods, exegetical styles, linguistic and contextual approaches, as well as their interpretations of the same Qur’anic verses. The findings indicate that Turjuman al-Mustafid functioned primarily as an instrument for religious education and doctrinal consolidation among early Malay Muslim communities, whereas Tafsir al-Azhar served as a reformist commentary addressing modern social, moral, and national issues in Indonesia. Both commentaries have significantly shaped Islamic religious practices, educational traditions, and intellectual discourses in the region. This study highlights the importance of understanding the interplay between text, interpreter, and socio-historical context in the evolution of Qur’anic exegesis in the Nusantara from classical to modern periods. Keywords: Turjuman al-Mustafid, Tafsir al-Azhar, Malay-Indonesian Qur’anic exegesis, comparativestudies, Qur’anic hermeneutics.